Steroid Cell Tumor NOS and Xanthogranulomatous Oophoritis: A Rare Association Mimicking Ovarian Malignancy - Saxena, Rushali; Singh, Smita; Agarwal, Kiran (Annals of Pathology and Laboratory Medicine, 2023)
Steroid cell tumor, NOS is an infrequently reported ovarian tumor, rarely presenting without endocrine symptoms. Xanthogranulomatous inflammation of ovaries is an extremely rare finding which often mimics malignancy on imaging. This case report presents a unique co-incidental finding of these two rare entities as incidental findings. A 44 year old female with previous history of total abdominal hysterectomy for leiomyoma presented with abdominal discomfort. Clinical examination revealed bilateral adnexal mass. Imaging suggested a possibility of bilateral ovarian mucinous cystadenocarcinoma. CEA, CA19-9 and CA125 were within normal limit. No signs and symptoms of endocrine manifestation were seen. Bilateral salpingo-oophorectomy specimen was sent for histopathological examination. Grossly, Left ovary showed a single yellow nodule measuring 1cm in diameter. Right ovary showed a gray tan cut surface. Microscopic examination revealed a left ovarian nodule composed of diffuse sheet of large tumor cell with abundant eosinophilic cytoplasm, round nucleus with a prominent nucleolus in a background of extensive vascular congestion. No reinke crystals, mitosis, necrosis, hemorrhage or nuclear atypia was seen. The tumor cells were immunopositive for Vimentin, Pan CK and Inhibin. Adjacent left ovarian stroma and right ovary showed features suggestive of XI. A diagnosis of Steroid cell tumor, NOS with xanthogranulomatous oophoritis was offered. Steroid cell tumor and xanthogranulomatous oophoritis, both are rare entities which may mimic malignancy. Awareness of these entities alone or in combination allows a clinician to avoid radical surgeries in such cases.